Double Higgs production and quadratic divergence cancellation in little Higgs models with T-parity - Dib, Claudio O.; Rosenfeld, Rogério [UNESP]; Zerwekh, Alfonso (Springer Nature, 2006)
We analyze double Higgs boson production at the Large Hadron Collider in the context of Little Higgs models. In double Higgs production, the diagrams involved are directly related to those that cause the cancellation of the quadratic divergence of the Higgs self-energy, providing a robust prediction for this class of models. We find that in extensions of this model with the inclusion of a so-called T-parity, there is a significant enhancement in the cross sections as compared to the Standard Model. © SISSA 2006.
Keywords: Beyond Standard Model; Hadron-Hadron Scattering; Higgs Physics